Effects of industrial noise pollution on the auditory performance and health status of industrial workers in Oluyole industrial estate, Ibadan, Nigeria (2017)
Exposure to excessive noise level is capable of producing destruction of the hair cells due to vasoconstriction of the cochlea blood vessels and over stimulation of the hair cells as a response to the noise exposure, which in turn may reduce the nutrient and oxygen to the cells as well as, placing a great impingement on the occupational performances of the Industrial workers. The study examined the potential effect of excessive noise exposure on the auditory performance and health status of some industrial workers in Ibadan. A total of hundred (100) industrial workers consisting of seventy-five (75) males and twenty-five (25) females were purposively selected to participate in the ex post facto research. Instruments used included a TENMA RS-232 Sound Level Meter (SLM) to measure the noise level of the bakery firm, Maico 53 audiometer to test the hearing levels of the participants, OMRON M2 Basic blood pressure monitor to assess the systolic, diastolic pressure and pulse rate of the participants and a self designed questionnaire to assess the participants’ daily health status. SLM readings of the firm revealed three different results of 85dB, 87dB and 91dB. 80% of the participants were affected by hearing loss on either right, left or both ears measured; 71% had high systolic blood pressure, 68% had abnormal pulse rate while 75% after exposure to excessive noise at work and 75% were not aware of the effects of excessive noise to their hearing organs as they were not informed at work. The Federal Government of Nigeria should enforce hearing conservation programme and health and safety regulations on every industry where noise is a by–product. In general, the health and safety of industrial workers should be placed on a high priority by government, employees and industrial employers.